2008
DOI: 10.1111/j.1601-5223.1992.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

The Triticeae as sources of hydroxamic acids, secondary metabolites in wheat conferring resistance against aphids

Abstract: NIEMEYER, H. M., COPAJA, s. V. and BARRIA, B. N. 1992. The Triticeae as sources of hydroxdmic acids, secondary metabolites in wheat conferring resistance against aphids. ~ Hereditas 116: 295-299. Lund, Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Mulch quantities obtained from the eight rye cultivars and the triticale cultivar (Trimaran) applied per pot before the sowing of the four warm-season weeds, and relative total quantities of benzoxazinoids 2,4-dihydroxy-1,4 (2H)-benzoxazin-3-one (DIBOA) and benzoxazolin-2(3H)-one (BOA). Niemeyer et al (1992), triticale does not contain benzoxazinoids, at least regarding the cv. Trimaran and in the experimental conditions described.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Mulch quantities obtained from the eight rye cultivars and the triticale cultivar (Trimaran) applied per pot before the sowing of the four warm-season weeds, and relative total quantities of benzoxazinoids 2,4-dihydroxy-1,4 (2H)-benzoxazin-3-one (DIBOA) and benzoxazolin-2(3H)-one (BOA). Niemeyer et al (1992), triticale does not contain benzoxazinoids, at least regarding the cv. Trimaran and in the experimental conditions described.…”
Section: Resultsmentioning
confidence: 98%
“…The present study, conducted in a greenhouse, aimed to examine the content of DIBOA and BOA in eight of the most recent and readily-available rye cultivars on the Italian market and to study the effect of mulches on four warm-season weeds. Since Niemeyer et al (1992) reported on the presence of DIBOA in triticale, it was decided to grow one cultivar of triticale used in the Po plain together with the eight cultivars of rye.…”
Section: Introductionmentioning
confidence: 99%
“…Aegilops speltoides is the most infested species. At the seedling stage this species contains a high amount of hydroxamic acids (Niemeyer et al, ), which is responsible for its high resistance to cereal aphids. Our results differ probably because of evaluation at a later stage of plant development, between flowering and fruiting.…”
Section: Resultsmentioning
confidence: 99%
“…These genes are located in chromosomes 4 and 5 of the three wheat genomes, and are involved in catalyzing the hydroxylation and ring expansion of indole-3-glycerol phosphate to synthesize DIBOA and DIMBOA (Frey et al 1997;Nomura et al 2003). Both DIBOA and DIMBOA are present in hexaploid wheat, however, only the latter appears to be present in high concentrations (Niemeyer et al 1992). Niemeyer et al (1992) found that the ancestor of A and D genomes of hexaploid wheat possesses low concentrations of hx, whereas Aegilops speltoides Tausch, the most likely donor of the B genome, and tetraploid wheat (AABB) possess high concentrations of DIMBOA, suggesting that the B genome is responsible for the main part of the synthesis of hx in hexaploid wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Both DIBOA and DIMBOA are present in hexaploid wheat, however, only the latter appears to be present in high concentrations (Niemeyer et al 1992). Niemeyer et al (1992) found that the ancestor of A and D genomes of hexaploid wheat possesses low concentrations of hx, whereas Aegilops speltoides Tausch, the most likely donor of the B genome, and tetraploid wheat (AABB) possess high concentrations of DIMBOA, suggesting that the B genome is responsible for the main part of the synthesis of hx in hexaploid wheat. From our results is not possible determine whether Rp1 is associated or not to Tbx genes, but it would be of great interest to analyze DIMBOA concentrations in the population.…”
Section: Discussionmentioning
confidence: 99%